2002
DOI: 10.1152/jn.2002.88.3.1387
|View full text |Cite
|
Sign up to set email alerts
|

Acute Topical Application of Tumor Necrosis Factor α Evokes Protein Kinase A-Dependent Responses in Rat Sensory Neurons

Abstract: Local perfusion of the dorsal root ganglion (DRG) with tumor necrosis factor alpha (TNF-alpha) in rats induces cutaneous hypersensitivity to mechanical stimuli. Thus we investigated the cellular mechanisms of TNF-alpha-induced mechanical hyperalgesia. The L(4) and L(5) DRGs with the sciatic nerves attached were excised from rats for in vitro dorsal root microfilament recording. After baseline recording for 15 min, TNF-alpha (0.001, 0.01, 0.1, or 1 ng/ml) was applied to the DRG for 15 min, followed by washout f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(55 citation statements)
references
References 30 publications
2
51
2
Order By: Relevance
“…Indeed, inflammatory cytokines acting locally may directly or indirectly stimulate and/or sensitize nociceptors, thereby contributing to sensory hyperalgesia (5,16). Previous work implicating TNF-␣ in the development of neuropathic pain follows the observation that exogenous TNF-␣ elicits a PKA-dependent response in rat sensory neurons (29). However, in the present study, TNF-␣ at concentrations considerably higher than that found in mesenteric lymph after LPS treatment did not stimulate mesenteric afferent discharge.…”
Section: Discussioncontrasting
confidence: 70%
“…Indeed, inflammatory cytokines acting locally may directly or indirectly stimulate and/or sensitize nociceptors, thereby contributing to sensory hyperalgesia (5,16). Previous work implicating TNF-␣ in the development of neuropathic pain follows the observation that exogenous TNF-␣ elicits a PKA-dependent response in rat sensory neurons (29). However, in the present study, TNF-␣ at concentrations considerably higher than that found in mesenteric lymph after LPS treatment did not stimulate mesenteric afferent discharge.…”
Section: Discussioncontrasting
confidence: 70%
“…For example, administration of tumor necrosis factor (TNF) to DRG in rats induces cutaneous hyperalgesia to mechanical stimuli. Conversely, blocking the activity of certain inflammatory cytokines in DRG partially relieves the CCD-induced hyperalgesia [16,17] . In addition, increased activity of satellite glial cells in the DRG has been recently shown to play an important role in CCD-induced neuronal hypersensitivity [18] .…”
Section: Discussionmentioning
confidence: 99%
“…To inhibit PKA activity, presynaptic neurons were incubated selectively in H-89 (Calbiochem, La Jolla, CA) (Zhang et al, 2002) or KT5720 (Calbiochem) (Diefenbach et al, 2000), which were dissolved in DMSO (final [DMSO] Ͻ0.01%). 8Br-cAMP (Research Biochemicals, Natick, MA) and acetylcholine were dissolved in water.…”
Section: Methodsmentioning
confidence: 99%